Perbaikan Postur Kerja Menggunakan Metode Rosa Dan CMDQ Pada Mie Kuning Putri Minang - Sepriana, rina; Susriyati, Susriyati; Harma, Beni (Jurnal Penelitian Dan Pengkajian Ilmiah Eksakta, 2025)
Office ergonomics is a branch of ergonomics that covers the entire work environment (workstations) as well as work tools (especially the use of computers and chairs) in offices. In modern office areas, most activities are carried out using a computerized system, so that all working time is carried out in a sitting working position. In essence, a human biomechanically needs to move in activities, not just stand or sit in only one position. Mie Kuning Putri Minang as the research object is located on Jalan Utara II, Seberang Padang, Padang Selatan District, Padang City, West Sumatra. The aim of this research is to improve work posture using the CMDQ (Cornell Musculoskeletal Discomfort Questionnaire) and ROSA (Rapid Office Strain Assessment) methods. ). The results of research using the CMDQ method show that employees complain about the neck, shoulders, arms, back, waist, hips, buttocks, and need immediate improvement. The results of the ROSA calculation show that employee A, employee B, and employee C have a high or dangerous risk, and urgent improvements need to be made. The cause of the high risk experienced is due to the inadequate facilities used, the need to update work facilities according to ergonomic standards in the world of work, and holding good and correct computer office ergonomics training to reduce injuries when using computers.